Gênese de horizontes subsuperficiais escuros de solos em área do Batólito Pelotas, RS. - Botelho, Márcio Ramos (2011)
Dark subsurface horizons with morphological characteristics similar to sombric horizonts have been found in southern Brazil, particularly in the higher areas of the Pelotas Batholith, located in the eastern portion of the Escudo Sul-rio-grandense. The sombric horizon, initially identified by soil scientists who worked in the Belgian Congo, constitutes a diagnostic horizon in soil classification systems of FAO and Soil Taxonomy, but not in the Brazilian system. The conception of sombric horizon in these classification systems is of a free draining subsurface horizon, containing iluvial humus not associated with aluminum or dispersible by sodium, with value and/or lower chroma than the overlying horizon. In the field it can be differentiated from the buried A horizon by monitoring lateral variations and in the laboratory by analyzing thin sections. The mechanisms responsible for the genesis of the sombric horizon are still poorly understood, although most authors agree on the illuvial humus origin and that it constitutes a diagnostic horizon. Considering the need to characterize the occurrence of such horizons in the region and the possible reasons for its genesis this work aimed to describe the occurrence of soil profiles exhibiting dark subsurface horizons with similar morphology to the sombric horizon in the region of Pelotas Batholith and to investigate the organic matter involved in the process. To achieve this goal physical, chemical, morphological, mineralogical and isotopic studies were performed in ten soil profiles with dark subsurface horizons, two of them without the sombric morphological characteristics and another one with morphological evidence of buried A horizon, and two degraded areas. The results showed that: a) the position of the dark subsurface horizons coincide with the A2, AB, BA horizons, top of B horizon or AC/CR; b) the horizons with morphology similar to sombric are not buried horizons, as indicated by particle size analysis, mineralogy, morphology and lateral variations of these horizons in the field, c) the fractionation of humic substances indicated a process of illuviation of organic matter, especially humic acids, for all soil samples, showing that the illuviation of organic material occurs not only in profiles with sombric horizons; d) the absence of the E horizon, associated with the Al + ½ Feo criteria, optical density of oxalate extract, chemical fractionation and significant presence of illuvial subsurface cutans indicate that the podzolization process is only incipient in the soil profiles; d) the C isotopic composition indicate that a part of the dark subsurface horizons have organic matter from C4-type plants (grasslands), differing from to the present. In other profiles, there is a mixture of C3 plants (forests) and C4 plants with little or no variation from the current vegetation, suggesting that the genesis of these horizons is not related only to changes in vegetation; f) a significant part of the soils located on the Pelotas Batholith present are not adequately classified in the Brazilian soil classification system, g) the adoption of the horizon or sombric character and changes in the Argissolos Bruno-Acinzentados suborder in future editions of the Brazilian System of Soil Classification would fit better a significant part of the soil profiles of the study area.